Demodex Infestation in Patients with Rosacea - Dursun Türkmen; Gamze Türkoğlu (Türkiye Parazitoloji Dergisi, 2019)

(untitled)
Objective:Although the etiology of rosacea is not known exactly, it is thought as a multifactorial disease. Demodex spp. are asymptomatic saprophytic ectoparasites living in hair follicles and sebaceous glands. The aim of this study was to investigate the frequency of Demodex spp. in patients with rosacea and compare with the control group by using superficial skin biopsy method.Methods:Seventy seven patients with rosacea and 31 control patients were included in the study. In patients, for the determination of density of Demodex spp., non-invasive standard superficial skin biopsy method was applied. Detection of ≥5/cm2 Demodex spp. was considered positive.Results:The mean age of the patients was 44.5±14.6 years and the mean age of the control group was 48.2±14.9 years. Of the patients, 55.1% had erythema-telangiectatic type, 43.5% had papulopustular type, and 3.9% had fimatous type lesions. Demodex infestation was positive in 33.8% of the patients with rosacea and this rate was 9.7% in the control group. Difference was statistically significant. There was no significant difference in Demodex spp. positivity in terms of gender in patients with rosacea.Conclusion:The importance of Demodex infestation in patients with rosacea has been increasing in recent years. Considering some studies conducted in our country, we think that the investigation of Demodex spp. in patients who are considered to have rosacea will be beneficial in the terms of early diagnosis and treatment.